PROGRAM DEVELOPMENT FOR DERIVATIVE FILTERS AND SEPARATION OF GRAVITY DATA ANOMALY USING MOVING AVERAGE AND TREND SURFACE ANALYSIS TECHNIQUES - Abdurrahman Jayadita, Muhammad
There are many gravity anomaly data processing techniques that can be used to identify the condition of subsurface geological structures based on rock density contrast parameters. In this research, a derivative anomaly calculation program was developed using the First Horizontal Derivative (FHD) and Second Vertical Derivative (SVD) 2D techniques, regional and residual anomaly separation programs were created using the Moving Average (MA) and Trend Surface Analysis (TSA) techniques, as well as a visualization program to display calculated data in the form of an anomaly map in order to gain an understanding of data processing techniques using the gravity method. Programs created using the Matlab R2021a programming language. Before being implemented in the research area, the program created was tested by performing calculations on several synthetic models whose results were compared with commercial software. The test results show that there is a conformity of the anomalous distribution pattern and the root mean square error value <0.01 µGal for the anomaly separation technique, <0.01 µGal/m for the FHD technique, and <0.01 µGal/m2 for the SVD technique. Next, the implementation of the program made in the Malingping geothermal area is carried out. The results of regional anomaly calculations using TSA range from 100 mGal to 135 mGal, while regional anomaly values using MA range from 100 mGal to 125 mGal. For residual anomaly values, the TSA results range from -6 mGal to 6 mGal, while the MA results range from -8 mGal to 8 mGal. Derivative calculation results show that the FHD anomaly is 1 mGal/m to 8 mGal/m and the SVD anomaly is -2 mGal/m2 to 1.5 mGal/m2. Based on the analysis of the TSA residual anomaly distribution map and the results of FHD and SVD anomaly calculations supported by geological information, several fault structures can be identified in a northwest-southeast direction and southwest-northeast direction